Immature Platelet Fraction in Patients with S LE-related Thrombocytopenia - Yeny Tanoyo; Andri Reza Rahmadi; Amaylia Oehadian (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Systemic lupus erythematosus (SLE) is an autoimmune disease which causes chronic inflammation and may impact various organs. Hematologic abnormality, including thrombocytopenia, is a common clinical manifestation in SLE, ranging between 7-30%. Thrombocytopenia in SLE has been proven to correlate with a more active disease and a worse prognosis. Most of the time, it gets hard to determine the underlying cause of thrombocytopenia. Immature platelet fraction (IPF) examines immature thrombocyte at peripheral blood and can be used to determine whether thrombocytopenia happens because of a decreased production or increased peripheral thrombocyte destruction. This study was done to evaluate immature platelet fraction value in SLE patients with thrombocytopenia. This was a cross-sectional descriptive observational study. Sample was taken from SLE inpatients and outpatients at Dr. Hasan Sadikin Bandung Hospital. There were 24 subjects included in this study, which counts 7.4% of SLE population. The mean platelet count was 56,870 ±28,933 /mm3. IPF values ranged from 0.9-3.2%, with median 5.7%. The median IPF in moderate-severe thrombocytopenia group was 7.5%, higher than that of mild thrombocytopenia group (4.2%). It can be concluded that IPF values were increased in most SLE patients with thrombocytopenia compared to normal population. It suggests that increased platelet destruction plays an important role in the pathogenesis of SLE thrombocytopenia. A wide range of IPF values shows multifactorial nature of thrombocytopenia causes in SLE patients.